The family dynamics of children on the streets of Ibadan, Southwest Nigeria - Abimbola M. Obimakinde; Moosa Shabir (South African Family Practice)
Background: Children roaming the streets estimated at 1 in 10 by a 2021 United Nation Children’s Funds (UNICEF) report is a growing problem, in cities of lower- and middle-income African countries. Studies of street children with no family ties abound, but there is a paucity of studies on children on the street who exist within families and return home daily. We explored the family dynamics of children on the streets of Ibadan, emphasising family structure, resources and relationships.